The Single Currency's Effects on Eurozone Sectoral Trade: Winners and Losers? - Claudio Vicarelli; Roberta De Santis; Sergio De Nardis (Kiel Institute for the World Economy (IfW), 2008)
In this paper we study the effect of the single currency across industries for euro area members. This analysis may help to shed light on the main factors influencing the euro effect on trade flows. We intend to verify whether these factors are specific to individual sectors and/or countries or common to the entire euro area. We use a dynamic specification of an augmented gravity equation. Following the most recent econometric literature, we apply a ?System GMM? dynamic panel data estimator (Blundell and Bond, 1998) to avoid inconsistency and biases in the estimates, and introduce controls for heterogeneity. Our preliminary results indicate some heterogeneity at country level. Despite statistically pro-trade effects in the majority of the EMU members, at sectoral level there are some countries in which the impact of the euro has been negative. The pro-trade effects are mainly concentrated in scale intensive industries. Industrial specialization and location of these industries, together with other factors (i.e. differences in factor endowments, product regulations across countries), may have determined ?the winners and the losers? in the monetary integration process. These preliminary findings are in line with those of the few other studies on this issue. In particular, this recent literature seems consistent with Baldwin?s (2006) ?new good? hypothesis. However, in our estimates the magnitude of these effects are lower, probably because of our empirical strategy. Moreover, the sector/country analysis points out that other specific factors have been in place in shaping differently the euro effect on trade.
Keywords: F33; C33; F14; F15; F4; 330; International trade; currency unions; gravity models; dynamic panel data; Blundell-Bond estimates